Entre mundos: um encontro com o outro na tessitura da narrativa jornalística - Priscila Martins Dionizio (2011)
Media scenario is seen as an outstanding place where symbolic exchange of ideas and the sharing of meaning occur in the contemporary society. The journalistic craft, as a discursive practice implied in this scenario, conects us to a variety of ethnics and cultures, creating narratives and figures of otherness. In this sense, the main point of this research is to think about the relations that are developed with otherness within journalistic production. For that, we studied Nova Africa, a journalistic series aired by TV Brasil. Based on this series, we came to realize the intervention of the interviewees in the construction of meaning in it. By analysing the interaction of the interviewees in the series, we asked ourselves if journalism as a practice can gather and reflect the other when talking about him.